PENGARUH STRATEGI COSTUMER RELATIONS PT BANK PANIN CABANG SIDOARJO TERHADAP LOYALITAS NASABAH TABUNGAN MIKRO PANIN - Afina Rusyida Saniy; Ainur Rochmaniah (Kanal: Jurnal Ilmu Komunikasi, 2015)
The purposes of this research to analyze and explain the influence of customer relations strategies in the PT. Panin Bank branch A. Yani Sidoarjo towards customer loyalty micro savings Panin. This research used quantitative research with survey research methods. Meanwhile, the subject of this study is micro panin savings customers as many as 100 customers were selected using purposive sampling technique. Partial test (t test) showed that strategy of customer campaign dependent as independent variables which are marketing campaign,customer campaign and service quality that is affected towards dependent variable, namely customer loyalty PT. Panin Bank branch A. Yani Sidoarjo. The simultant test (Test F) indicated that the customer campaign strategy dependent as independent variables which are marketing campaign, customer campaign and service quality are affected towards dependent variable, namely customer loyalty PT. Panin Bank branch A.Yani Sidoarjo. Results analysis of the determination (R2) coefficient indicated that there is a relationship between all independent variables namely marketing campaign, customer campaign and service quality towards dependent